2021
DOI: 10.1007/s00402-021-03790-7
|View full text |Cite
|
Sign up to set email alerts
|

Unicondylar knee replacement versus total knee replacement for the treatment of medial knee osteoarthritis: a systematic review and meta-analysis

Abstract: Background Since the optimal surgery for isolated medial knee osteoarthritis (OA) is unclear, this study aimed at comparing the effectiveness of unicondylar knee replacement (UKR) with total knee replacement (TKR) for simple medial knee OA. Methods Literature searches of PubMed, Embase, Web of Science, and the Cochrane Library were searched up to 1th April 2020. Only studies comparing UKR with TKR for isolated medial knee OA were included. Data collection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 40 publications
1
9
1
11
Order By: Relevance
“…10,11 Meta-analysis results comparing UKA and TKA in terms of knee function differ from past to present. Arirachakaran et al 14 reported that there was no difference in postoperative function, but in a very recent meta-analysis, Deng et al 15 showed that UKA effectively improved knee function more than TKA at early and mid-term follow-up, with no Although UKA had better postoperative knee function than TKA in our study, we could not find a relationship between knee function and joint awareness. However, joint awareness is one of the issues to be considered in gaining a high level of activity in young patients with high expectations.…”
Section: Discussioncontrasting
confidence: 72%
“…10,11 Meta-analysis results comparing UKA and TKA in terms of knee function differ from past to present. Arirachakaran et al 14 reported that there was no difference in postoperative function, but in a very recent meta-analysis, Deng et al 15 showed that UKA effectively improved knee function more than TKA at early and mid-term follow-up, with no Although UKA had better postoperative knee function than TKA in our study, we could not find a relationship between knee function and joint awareness. However, joint awareness is one of the issues to be considered in gaining a high level of activity in young patients with high expectations.…”
Section: Discussioncontrasting
confidence: 72%
“…Основними варіантами хірургічного лікування медіального гонартро зу є МЕП та ТЕП КС [3]. Однак питання вибору оптималь ного варіанту ендопротезування досі залишається дискусійним [8,9].…”
Section: вступunclassified
“…Як правило, ортопеди використовують одну конкретну форму ендопротезування на основі їх попередньої підготовки, ін дивідуальних уподобань та клінічного досві ду [1]. Однак рішення щодо вибору типу втручання має бути обґрунтованим на основі клінічних даних з урахуванням індивідуаль них потреб пацієнта та наявних персоніфікованих факторів [8,9].…”
Section: результати огляду літературних джерелunclassified
See 1 more Smart Citation
“…Surgical treatment, such as microfracture surgery, arthroscopic debridement, unicompartmental knee arthroplasty (UKA), total knee arthroplasty, etc. ( Deng et al, 2021 ; Katz et al, 2021 ) ( Table 1 ). Conservative treatment is mainly used to relieve pain symptoms, but cannot effectively prevent or reverse the progression of OA ( Hochberg et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%